Retrospective analysis of colonoscopy findings in symptomatic patients under 50 years - Zainal Abidin, Fatimah Nabilah; Elagili, Faisal; Md Nor, Azmi; Salmi, Irfan (Wiley`, 2025)
Aim: Colonoscopy is done in younger patients nowadays despite benign nature of disease in majority of this population. The diagnostic yield of colonoscopy has been considered one of the measures for appropriateness of colonoscopy in young adult. This study aim to evaluate the yield of colonoscopy in young adults whom are symptomatic.